A Queer('s) Cinema. - Betancourt, Manuel (Film Quarterly, 2019)
Queer cinema, no matter how rebellious, is the child of straight cinema-its bastard child, perhaps, but its progeny no less. Queer cinema must push against decades of tradition to create itself anew. Borrowed genres and hand-me-down narratives have served their purpose. If the (curated though not novel) propositions and (recent though not unique) examples that follow point anywhere, it is to a still-to-be-imagined future where queer cinema can continue to expand while never ceding its right to be "nice" in order to serve those it portrays.
Num Pages: 15-17
Keywords: 1-Cinéma; 2-Genre et sexualité; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Créateur.rice LGBTQ+; 5-Créateur.rice PANDC; _Nettoyé